Comparative analysis of snap techniques in young weightathleters at the initial and training stages of sports training - Shalmanov, A. A.; Skotnikov, V. F. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to compare general and specific criteria for snatch technique among young weightlifters at the initial (26 people aged 9-12 years) and training (129 people aged 13-17 years) stages of sports training.